2020
DOI: 10.1007/978-3-319-15877-8
|View full text |Cite
|
Sign up to set email alerts
|

Encyclopedia of Couple and Family Therapy

Abstract: part of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Sociologists have found that negative emotion often occurs when we perceive ourselves as not getting what we deserve (Turner, 2007). If we integrate the sociology of emotion into, say, experiential therapy (McDowell et al, 2018), we are better able to link societal dynamics with intimate family experiences in ways that enhance and contextualize emotional expression and the sharing of wants and needs. Generally those with more power and influence experience more positive emotions, particularly when they feel that they are getting the rewards and respect they deserve.…”
Section: Third-order Thinkingmentioning
confidence: 99%
See 4 more Smart Citations
“…Sociologists have found that negative emotion often occurs when we perceive ourselves as not getting what we deserve (Turner, 2007). If we integrate the sociology of emotion into, say, experiential therapy (McDowell et al, 2018), we are better able to link societal dynamics with intimate family experiences in ways that enhance and contextualize emotional expression and the sharing of wants and needs. Generally those with more power and influence experience more positive emotions, particularly when they feel that they are getting the rewards and respect they deserve.…”
Section: Third-order Thinkingmentioning
confidence: 99%
“…From an attachment perspective, she wants to know more not only about the working models of relationships they have each internalized but also how their perceptions of belonging and connection are related to social locations and societal power and how these support or interfere with attachment bonds (McDowell et al, 2018). She is aware that the mental health services system is one of the systems of systems at work in their lives.…”
Section: Juliamentioning
confidence: 99%
See 3 more Smart Citations